Two-mode network modeling and analysis of dengue epidemic behaviour in Gombak, Malaysia - Malik, Hafiz Abid Mahmood; Mahesar, Abdul Waheed; Abid, Faiza; Waqas, Ahmad; Wahiddin, Mohamed Ridza (Elsevier, 2017)
Many complex systems in the form of network have been a great focus of research in the last decade. In fact, various domains have been modeled and analyzed as complex networks ranging from biological, technological, transportation, social and many others. The phenomenon of distribution of many dengue cases has been a great concern in Malaysia in recent years. Therefore, in this work we formalize and analyze the dengue spreading phenomenon from the perspective of complex network and model the dataset of dengue affected cases in Gombak, Selangor (Malaysia) into two-mode network. By using the real dataset of dengue cases in Malaysian states obtained from the Malaysian Health Ministry, we observe this network with global (Closeness, Betweenness and Short path-length)and local (Degree and Clustering coefficient) structure perspectives. We further formalize it by projecting from two-mode network using three methods of network projection. From the network analysis, we found that there are few localities that were affected again and again throughout the year. Further, few localities have high number of dengue cases as compared to others. From the global structures perspective, very few localities have shown closeness to all other localities and therefore easing the route for the propagation of dengue virus that has the highest weight in terms of number of dengue cases.